Impact of Floods on the Socio-Economic Conditions of Communities in Sungai Tabuk - Mutiani, Mutiani; Rusmaniah, Rusmaniah; Triyono, Sigit; Jumriani, Jumriani; Febrian, Muhammad Ikhsan (Program Studi Pendidikan IPS, 2024)
High rainfall resulted in flooding in the Sungai Tabuk area. Floods have had a complex impact on the socio-economic conditions of the community. Analysis of the impact of floods is needed to design post-disaster community development strategies. The purpose of this research is to describe the social and economic impacts of floods in Sungai Tabuk. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the impact of flooding on social conditions included: 1) demographic conditions of the population who experienced changes in social structure, 2) decreased health conditions, 3) decreased quality of education, 4) damage to housing, while the impact of flooding on economic conditions included: 1) loss of livelihood, 2) decrease in income, 3) damage to crops and loss of valuable documents.